2013
DOI: 10.1016/j.jvs.2013.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Characteristics and Natural History of Renal Artery Aneurysms During Longitudinal Imaging Surveillance

Abstract: There were a total of 312 CAS procedures (n ¼ 299 patients) and 344 CEA procedures (n ¼ 335) in this time period. For patients who had reoperation on the same carotid vessel (n ¼ 5 for CAS, n ¼ 5 for CEA), we used the last documented ultrasound prior to the date of reoperation. These ultrasounds were used to identify ECA occlusions and in-stent restenosis using consensus panel velocity criteria.Results: There were 210 CAS patients with follow-up ultrasounds (67%), and there were 207 CEA patients with follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 0 publications
2
13
1
2
Order By: Relevance
“…Therefore, mean rate of aneurysm growth appears highly variable and seems to be related to the initial diameter. In the authors' experience, rapid growth is rare for small aneurysms and this observation is consistent with the data from the studies of Klausner et al and Wayne et al 24,25 For these lesions, imaging follow up can be less frequent. Conversely, surgery is indicated in cases of rapid diameter growth.…”
Section: Indication For Treatmentsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, mean rate of aneurysm growth appears highly variable and seems to be related to the initial diameter. In the authors' experience, rapid growth is rare for small aneurysms and this observation is consistent with the data from the studies of Klausner et al and Wayne et al 24,25 For these lesions, imaging follow up can be less frequent. Conversely, surgery is indicated in cases of rapid diameter growth.…”
Section: Indication For Treatmentsupporting
confidence: 89%
“…Klausner et al and Wayne et al have studied the evolution of renal artery aneurysms and reported particularly slow growth, <1 mm per year. 24,25 In the present study, mean diameter growth was higher, rising to 9.2 mm in 36 months with a median growth of 3.1 mm per year. The difference between the present series and the two other publications may be explained by different patient profiles.…”
Section: Indication For Treatmentcontrasting
confidence: 40%
“…2 Most ruptures are diagnosed at the time of presentation, and several authors have supported no rupture during the surveillance of nonoperative RAAs. 1,2,4,5,[7][8][9][10][11] Contemporary series estimate a median annualized growth rate of 0.06 to 0.6 mm. [9][10][11] The most recent and largest multiinstitutional series of nonoperative RAA surveillance found no difference in growth rate based on aneurysm morphology or calcification.…”
Section: Incidence and Natural Historymentioning
confidence: 99%
“…1,2,4,5,[7][8][9][10][11] Contemporary series estimate a median annualized growth rate of 0.06 to 0.6 mm. [9][10][11] The most recent and largest multiinstitutional series of nonoperative RAA surveillance found no difference in growth rate based on aneurysm morphology or calcification. 10 These same authors also report the successful surveillance of 88 aneurysms measuring 2 to 3 cm and seven aneurysms measuring >3 cm without complication or rupture during a mean of 49 months.…”
Section: Incidence and Natural Historymentioning
confidence: 99%
See 1 more Smart Citation